IMPLEMENTATION OF LOCAL CULTURE-BASED SCHOOL PROGRAMS IN PUBLIC HIGH SCHOOLS ACROSS MERAUKE REGENCY - Maturbongs, Lodovika; Lestari, Slamet (Multidisciplinary Indonesian Center Journal (MICJO), 2025)
This study aims to determine (1) the implementation of local culture-based school programs in public senior high schools throughout Merauke Regency. (2) the supporting factors for the implementation of local culture-based school programs in public senior high schools throughout Merauke Regency. (3) the inhibiting factors for the implementation of local culture-based school programs in public senior high schools throughout Merauke Regency. This study is a qualitative study. Data collection techniques used observation, interviews, and documentation. Data validity was verified using source triangulation and technical triangulation. Data analysis included data condensation, data presentation, and drawing conclusions. The results of this study are: (1) the implementation of local culture-based school programs in public senior high schools throughout Merauke Regency is carried out through various activities, such as competitions, craft making, and art performances. (2) several supporting factors for the implementation of local culture-based school programs in public senior high schools throughout Merauke Regency, such as support from educators, teachers, students, and parents. (3) There are several inhibiting factors in the implementation of local culture-based school programs in State Senior High Schools throughout Merauke Regency, such as the entry of foreign cultures, time management challenges, and so on.